2003
DOI: 10.1186/1471-2091-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Distal hinge of plasminogen activator inhibitor-1 involves its latency transition and specificities toward serine proteases

Abstract: Background: The plasminogen activator inhibitor-1 (PAI-1) spontaneously converts from an inhibitory into a latent form. Specificity of PAI-1 is mainly determined by its reactive site (Arg346-Met347), which interacts with serine residue of tissue-type plasminogen activator (tPA) with concomitant formation of SDS-stable complex. Other sites may also play roles in determining the specificity of PAI-1 toward serine proteases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…However, in light of our Michaelis complex model and the available crystal structure of active PAI-1, Asp-355 is unlikely to provide an electrostatic contact with the VR1 of tPA. Rather, the side chain of Asp-355 may contribute to the intramolecular hydrogen bond network found within the ␤-sheet C, thereby playing an important structural role in PAI-1, as other studies have suggested (43). Alternatively, other surface-exposed regions in tPA, such as the kringle domains (13), might facilitate binding to PAI-1.…”
Section: Table IV Gibbs Free Energy Of Activation Associated With Reamentioning
confidence: 90%
See 1 more Smart Citation
“…However, in light of our Michaelis complex model and the available crystal structure of active PAI-1, Asp-355 is unlikely to provide an electrostatic contact with the VR1 of tPA. Rather, the side chain of Asp-355 may contribute to the intramolecular hydrogen bond network found within the ␤-sheet C, thereby playing an important structural role in PAI-1, as other studies have suggested (43). Alternatively, other surface-exposed regions in tPA, such as the kringle domains (13), might facilitate binding to PAI-1.…”
Section: Table IV Gibbs Free Energy Of Activation Associated With Reamentioning
confidence: 90%
“…Whether or not interactions implicated in PAI-1 binding are completely electrostatic in nature is yet to be determined. Moreover, we cannot rule out a possible structural role for either distal loop residues, as other studies involving active-to-latent transitions suggest that P4Ј and P5Ј substitutions contribute to the stability of the native (active) structure of PAI-1 (43,44). Nonetheless, our results demonstrate for the first time the critical importance of the proposed exosite interactions between the VR1 of tPA and the distal P4Ј and P5Ј residues of PAI-1 in promoting the proper orientation of the scissile bond at the active-site pocket for subsequent cleavage and loop insertion in the serpin and hence the distortion of the target proteinase.…”
Section: Table IV Gibbs Free Energy Of Activation Associated With Reamentioning
confidence: 99%
“…Tenecteplase (TNK-tPA) is a newer generation of tPA variant showing slower inhibition by PAI-1 [6] . Extensive studies to understand the molecular interactions between tPA and PAI-1 have been carried out [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , however, the precise details at atomic resolution remain unknown. We report the crystal structure of tPA·PAI-1 complex here.…”
mentioning
confidence: 99%